Impact of weight cycling on risk of morbidity and mortality. Issue 11 (29th September 2014) - Mehta, T.; Smith, D. L.; Muhammad, J.; Casazza, K.
Summary Unintentional weight gain is commonly observed in adult humans, often provoking intentional weight loss attempts followed by unintentional weight regain. This episodic variation in body weight over a period of time has been referred to as 'weight cycling'. Over the last two decades, weight cycling has been associated with a number of morbid health conditions and increased mortality. This article provides a comprehensive evaluation of recent weight‐cycling evidence, looks to understand design differences between studies and study outcomes, assesses the need for further research on particular health outcomes, and proposes alternative methodologies that will bridge the needs and capabilities of research. Searches were conducted per PRISMA guidelines. Articles on weight cycling in the literature were initially identified using search strings in PubMed. Eligibility assessment of the remaining articles was performed independently by three reviewers to identify publications that presented direct evidence. Twenty human studies (in addition to seven animal studies) were selected and retained; 12 accounted for the intentionality of weight loss. Although weight regain following successful weight loss remains one of the most challenging aspects of body‐weight regulation, evidence for an adverse effect of weight cycling appears sparse, if it exists at all.